The Divine and the Vulnerable: Towards a Political (A)Theology of Uncertainty - Nicolás (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2025)
This article aims to address some philosophical and theological reflections on the notions of vulnerability and uncertainty, which in times of pandemic have become dimensions of sociopolitical, religious, and cultural re-signification. The hypothesis of this paper is that the impossibility of dealing with these existential dimensions has to do with the impact of modernity on ways of thinking about politics and even religion to this day. From this point, some lines of theological reflection will be proposed that allow us to politically address the dimensions of vulnerability and uncertainty in social terms, taking them as epistemic and hermeneutical elements from which to think about the divine and faith.
Keywords: vulnerability; uncertainty; pandemic; atheology; political theology